2019
DOI: 10.3892/or.2019.6966
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin induces an anti‑tumor effect on murine mammary cancer via p38‑dependent apoptosis

Abstract: Breast cancer is the most common malignancy in women. Apoptosis is important for tumor suppression and may delay cancer progression. It was found that shikonin induced apoptosis in 4T1 murine mammary cancer cells and MDA-MB-231 human breast cancer cells in vitro. Total p38 and c-Jun N-terminal kinase (JNK) levels were maintained in 4T1 cells, and p38 phosphorylation, but not JNK phosphorylation, was significantly increased. Caspase-3/7 activity was detected, which suggested that the p38 pathway, but not the JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Shikonin, a natural naphthoquinone component extracted from the root of Lithospermum erythrorhizon and Arnebia euchroma (Royle) Johnst native to China, hold promising potentials for antitumor effects via multiple-target mechanisms. [4][5][6][7][8] It was reported that the anti-migration and anti-invasion activities of shikonin was through inhibition of c-Met followed by suppression of epithelial-mesenchymal transition (EMT) in lung cancer cells. 9 Shikonin showed to exert anticancer effects on gallbladder cancer (GBC) cells by inducing apoptosis and regulating the cell cycle arrest via the c-Jun N-terminal kinase (JNK) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin, a natural naphthoquinone component extracted from the root of Lithospermum erythrorhizon and Arnebia euchroma (Royle) Johnst native to China, hold promising potentials for antitumor effects via multiple-target mechanisms. [4][5][6][7][8] It was reported that the anti-migration and anti-invasion activities of shikonin was through inhibition of c-Met followed by suppression of epithelial-mesenchymal transition (EMT) in lung cancer cells. 9 Shikonin showed to exert anticancer effects on gallbladder cancer (GBC) cells by inducing apoptosis and regulating the cell cycle arrest via the c-Jun N-terminal kinase (JNK) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed to reduce breast cancer stem cell load and tumorigenic potential by inhibiting STAT3, FAK and Src mediated pathways and estrogen signaling [33][34][35]. SHK induced cell cycle arrest and p38-dependent apoptosis in breast cancer [36,37]. It also enhanced sensitivity of breast cancer cells to endocrine therapy and paclitaxel [38,39].…”
Section: Discussionmentioning
confidence: 93%
“…基于阿卡宁的结构修饰 相比于紫草宁而言,针对其对映异构体阿卡宁的结构修饰工作相对较少,主 要是我国学者报道了一些研究进展(图 7) 。为了进一步提高阿卡宁对肿瘤细胞 作用的选择性,Wang 等 [100,101] 对阿卡宁的萘醌环和支链羟基同时进行修饰,得 到了阿卡宁衍生物(4a) ,随后又获得阿卡宁肟(4b) 。为了进一步研究紫草宁/ 阿卡宁肟 DMAKO 的抗肿瘤活性靶点,Huang 等 [108] 又针对阿卡宁肟进行了一系 列乙酰化和泛素化修饰(4c)。 He 等 [93] 为了提高阿卡宁对端粒酶的结合能,对阿 卡宁的支链羟基进行糖基化修饰获得了阿卡宁糖苷(4d)。 [109,110] 或途径抑制乳腺癌、肺癌、肝癌、结肠癌、 胶质瘤等肿瘤的生长(参见表 3)。 以下分别针对全球发病率排序靠前的癌症--乳腺癌、肺癌、结肠直癌、胃癌、肝癌、甲状腺癌、胰腺癌、血癌、黑色素瘤 及骨肉瘤,简述近年来有关紫草宁抑制各类肿瘤增殖的研究进展。 4.1.1. 紫草宁对乳腺癌的抗癌作用 在抗乳腺癌增殖方面 ,研究者 [111] 发现紫草宁可以通过调节 miR-17-5p/ Phosphatase and tensin homolog(PTEN)/ protein kinase B(Akt)通路或抑制基 质金属蛋白酶(matrix metallopeptidase, MMP)2/9 [112] 的活化,阻止乳腺癌细胞 迁移和侵袭; 紫草宁还可以诱导小鼠乳腺癌细胞经 p38 依赖性途径发生凋亡 [113] ; 可诱导雌激素受体 (estrogen receptor, ER) 阳性细胞 MCF-7 发生坏死和凋亡 [114] ; 还可通过抑制丙酮酸激酶(pyruvate kinase, PK)M2 的表达,增强紫杉醇对三阴 性乳腺癌的治疗效果 [115] [116][117][118] 。另有研究报道,紫草宁以 PI3K/Akt 信号通路为靶点,能够克服阿 法替尼治疗 NSCLC 的耐药性 [119] 。 Yeh 等研究表明紫草宁通过 p53 介导的细胞凋 亡途径对 A549 肺癌细胞具有潜在的和剂量相关的细胞毒作用,为临床上治疗肺 癌提供了一种有前途的辅助化疗候选药物 [120] 。在基础的机制研究方面,紫草宁 能激活活性氧(reactive oxygen species, ROS)介导的内质网应激反应,从而使 NSCLC 凋亡 [121] 。另外,紫草宁通过抑制整合素 1 表达和抑制细胞外信号调节激 酶(Extracellular signal regulated kinase, ERK)1/2 信号通路活性,减弱 NSCLC 对细胞外基质的粘附和转移能力 [122][123][124] [125] 。另有研究发现紫草 宁也可通过调节 p53, 核因子 E2 相关因子 2 (nuclear factor E2-related factor 2, Nrf2) 以及 ROS 依赖性途径诱导细胞凋亡 [126] 。细胞增殖是通过细胞周期来完成的,因 此细胞周期的每个检验点对于细胞正常增殖非常重要, 许多抗癌药物也是通过阻 滞细胞周期发挥其活性的。研究发现 [127] 紫草宁可通过抑制缺氧诱导因子阻滞结 肠癌细胞周期,从而抑制细胞增殖。在细胞自噬方面,紫草宁可靶向调节 galectin-1 和 c-Jun N-terminal kinase(JNK)信号通路或抑制 Yes 相关蛋白 (Yes-associated protein, YAP)表达,诱导结肠癌自噬 [128] 。此外,紫草宁还表现 出显著的抗胃癌活性,例如紫草宁通过抑制早期生长反应 1(Egr1)介导 p21 基 因表达诱导人胃癌细胞周期阻滞 [129] ;还可通过 toll 样受体 2(toll-like receptor 2, TLR2)-和核因子 kappa-B (nuclear factor kappa-B, NF-κB)介导的信号途径, 抑制胃癌细胞侵袭和迁移 [130][131][132] 。 4.1.4. 紫草宁对甲状腺癌和胰腺癌的抗癌作用 紫草宁抑制甲状腺癌和胰腺癌增殖的功能主要是通过诱导细胞凋亡和自噬 以及抑制细胞迁移和侵袭而实现。其中,抗甲状腺癌机制是通过降低 DNA 甲基 转移酶 1(DNMT1)或失活 PI3K/AKT 信号通路活性,抑制甲状腺癌细胞的生 长、 迁移和侵袭 [133,…”
Section: 达M9培养条件下的2倍。unclassified